A comparison between the effects of low (1 ?g) and standard dose (250 ?g) ACTH stimulation tests on adrenal cortex functions with leprosy patients - Çolak, R; Ozkan, Y; Önen, SE; Saral, Y; Halifeoglu, I (Taylor & Francis Inc, 2005)
Leprosy is a chronic granulomatous disease that either remains localized or widespread depending on the immunological status of the affected patient. It can lead to clinical or subclinical adrenal failure by influencing adrenal steroidogenesis. In the present study, 26 patients (21 males and 5 females) who were diagnosed with lepromatous leprosy and 15 healthy individuals who were compatible with the patients in terms of age and sex were subjected to an adrenocorticotrophic hormone (ACTH) stimulation test. The leprosy and control groups were subjected to 1 mu g low dose (LDT) and 250 mu g intravenous standard dose (SDT) ACTH stimulation tests after 12-hour nocturnal fasting with an interval of three days. Cortisol responses in 0, 30, and 60 minutes were examined. There was no difference between leprosy and control groups in terms of mean baseline cortisol values. Mean value of the peak cortisol response to both LDT and SDT was found to be significantly lower in the leprosy group than in the control group (p < 0.001 and p < 0.01, respectively). Peak cortisol response to LDT in the leprosy group was found below 20 mu g/dL in 9 patients (34.6%). As for the peak cortisol response to SDI; it was lower than 20 mu g/dL in 5 patients (19.23%). It was found that LDT response was abnormally low in 4 patients (15.38%) who responded normally to SDT. It was observed that there could be a decrease in adrenocortical reserve capacity although baseline adrenocortical functions were normal in patients with leprosy. It was seen that LDT was more sensitive than SDT in identifying this decrease.
Keywords: leprosy; adrenal failure; ACTH stimulation test